THREATS TO LOVE: FR. JÓZEF TISCHNER’S REFLECTIONS - Kępińska-Walczak, Zofia (Warszawskie Studia Pastoralne, 2016)
In his reflections, Father Józef Tischner devoted much attention to love – one of the theological virtues, which constitute the foundations of the Christian life. He wrote not only about what love and its characteristics are, but also about threats to love. This paper discusses the various dangers associated with love, and concludes that the only thing that can conquer these dangers is love itself. Therefore, we should cherish love all the time, following the example of evangelical love.